1999
DOI: 10.1038/sj.bjc.6690349
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, clinical and pathological effects of relaxation training and guided imagery during primary chemotherapy

Abstract: SummaryThe diagnosis and treatment of breast cancer are stressful, and stress may be associated with a poorer response to chemotherapy. There is a need, therefore, to develop and evaluate interventions that might enhance quality of life and, possibly, improve treatment response. The effects of relaxation combined with guided imagery (visualizing host defences destroying tumour cells) on quality of life and response to primary chemotherapy, to date, have not been adequately evaluated. Ninety-six women with newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(119 citation statements)
references
References 46 publications
6
109
1
3
Order By: Relevance
“…Despite the commonality of its use for physical disorders, there have been relatively few tests of relaxation usage and outcomes (Walker et al, 1999). Antoni et al (2006) reported effects not with relaxation frequency but with patients' reported confidence in their ability to use relaxation.…”
Section: Treatment Utilization and Outcomementioning
confidence: 99%
“…Despite the commonality of its use for physical disorders, there have been relatively few tests of relaxation usage and outcomes (Walker et al, 1999). Antoni et al (2006) reported effects not with relaxation frequency but with patients' reported confidence in their ability to use relaxation.…”
Section: Treatment Utilization and Outcomementioning
confidence: 99%
“…there is potential, therefore, for stress-reducing CAM interventions to influence the immune system via this neuroendocrine pathway. a number of previous randomised trials evaluating the effects of various behavioural, psychosocial and complementary therapies in cancer patients have demonstrated both improvements in quality of life as well as changes in biological parameters (38)(39)(40)(41)(42)(43). however, diagnostic and therapeutic heterogeneity, as well as the use of different tumour types and outcome measures, limit the conclusions that can be drawn.…”
Section: Introductionmentioning
confidence: 94%
“…however, diagnostic and therapeutic heterogeneity, as well as the use of different tumour types and outcome measures, limit the conclusions that can be drawn. previous research on breast cancer patients has shown that patients do not always comply with relaxation and guided imagery (38,42); therefore, the present study was designed to evaluate an alternative well-received intervention to promote relaxation. Hence, the current randomised controlled trial evaluated the effects of reflexology and scalp massage on host defences and neuroendocrine function.…”
Section: Introductionmentioning
confidence: 99%
“…The six subscales can be summated to obtain a single total score. Reliability and validity have been found to be good (Anderson et al, 2000), and the scale has been shown to be responsive to the effects of cancer therapies (Walker et al, 1997(Walker et al, , 1999a, psychological interventions (Walker et al, 1999b) and work-induced stress. It takes approximately one minute to complete (Anderson et al, 2000).…”
Section: Tolerance Assessmentmentioning
confidence: 99%